Developing features of self-educational competence for students of medical college - Dovmantovych, Nataliya; Dovmantovych, Mariіa (ScienceRise: Pedagogical Education, 2017)
The features of self-educational competence formation of students of medical colleges were analyzed in the article. The methods of diagnostics of criteria of self-educational competence of future specialists were presented. The main motivations of students’ entrance to medical college, their importance in formation of self-educational competence were elucidated. The initial level of knowledge of natural school disciplines was determined. The directions of formation of self-educational competence in students of medical college were outlined. The aim of research is to elucidate the features of self-educational competence of students of medical colleges by revelation and analysis of motives hierarchy of students’ learning. For studying the motives of entrance to medical college, the first year students were interrogated using the questionnaire “Motivation of study in educational institution”. The analysis of the results, received by this method, demonstrates that most students chose the motive “to get a diploma”. It was also revealed, that the level of interest to the natural-scientific disciplines is insufficient. That is why certain arrangements, directed on integral understanding of reality and advantages of own specialty and acquisition of abilities and skills of self-educational competence, must be realized. So, the modern professional education must provide the fast movement to self-education. The solution of this problem is closely connected with modernization of the content of professional education, with optimization of methods and technologies of organization of educational process, reinterpretation of its result